Microbial acid production by indigenous microorganism from ananas cosmosus - Yashini, K.Selvanathan (2021)
Threatened with the gradual and inescapable exhaustion of the earth's fossil energy resources, fermentative acid production from renewable biomass to replace the conventional petrochemical process is receiving an increasing amount of attention. Microbial acids production from fruit waste to compensate for the wastage from fruit industries, including pineapple fruit, can be seen as one of the feasible approach. Peel, core, stem, and leaves from the pineapple plant are attractive, abundant, cheap, and nonfood competitive biomass feedstock for microbial acid production. Current microbial acid production uses specific strains which require particular condition to grow. The diversity of the produced acid was limited to the strain metabolism. To date, there is no study reported on using indigenous microorganisms from the pineapple waste and using such waste as the carbon source for microbial acid fermentation. This study had work on a statistical optimisation for microbial acid production from indigenous microorganisms in the pineapple peel. The works involved were factors screening using Full Factorial Design (FFD) to determine the significant one, followed by a statistical optimisation process using Central Composite Design (CCD) of Response Surface Methodology (RSM). Study on the physicochemical, quality, and functionality of the produced microbial acid were also carried out. The performance of the fermentation process was evaluated based on the percentage of acidity (%). The optimised condition for the fermentation of pineapple peel using indigenous microorganisms was achieved at 27 °C, with 7 %glucose addition to the pineapple peel juice. The fermentation was carried out aerobically for five days without adding yeast. The condition of fermentation, such as sugar and mode of fermentation, was identified to affect the acid production in which showing the Crabtree effect. The produced microbial acid was characterised based on its physicochemical, quality, and functionality. The microbial acid contained 3.18 % reducing sugar, 4.0 % sucrose, 1.03 % ethanol, and 3.03 % acids, mainly acetic, malic, and citric acid with pH of 3.16 and 8.0 °8rix total soluble solid. Meanwhile, for the quality and functionality, the microbial acid produced contained 1.43 mg equi. ANI OOmL ascorbic acid and 82.06 % free-radical scavenging activity of antioxidant. In conclusion, microbial acid production by indigenous microorganisms from pineapple peel was successfully optimised using RSM. Although with lower acid content than the commercial microbial acids, its quality was at par.